High prevalence of norovirus GII.4 Sydney among children with acute gastroenteritis in Bangladesh, 2018-2021 - Nadim Sharif; Shamsun Nahar Ahmed; Nazmul Sharif; Khalid J. Alzahrani; Meshari A. Alsuwat; Fuad M. Alzahrani; Shamim Khandaker; Nuzhat Haque Monifa; Shoko Okitsu; Anowar Khasru Parvez; Hiroshi Ushijima; Shuvra Kanti Dey (Elsevier, 2023)
Background: Active molecular surveillance and rapid diagnosis method to track an outbreak of norovirus in Bangladesh is lacking. This study aims to determine the genotypic diversity, molecular epidemiology and evaluate a rapid diagnosis method. Methods: A total of 404 fecal specimens were collected from children aged below 60 months from January 2018 to December 2021. All samples were analyzed by reverse transcriptase polymerase chain reaction molecular sequencing of partial VP1 nucleotide. Immunochromatography kit (IC, IP Rota/Noro) was evaluated against reference test method. Results: We found norovirus in 6.7 % (27 of 404) fecal specimens. A wide diversity of norovirus genotype including GII.3, GII.4, GII.5, GII.6, GII.7, and GII.9 were detected. Norovirus strain GII.4 Sydney-2012 was the most predominant (74 %, 20 of 27) followed by GII.7 (7.4 %), GII.9 (7.4 %), GII.3 (3.7 %), GII.5 (3.7 %) and GII.6 (3.7 %), respectively. Co-infection of rotavirus and norovirus (19 [4.7 %] of 404) was the most prevalent. We found higher odds of prolonged health impact [OR 1.93 (95 % CI 0.87-3.12) (p = .001)] among patients with co-infection. The incidence of norovirus was significant among the children below 24 months (p = 0.001). Significant relation of temperature with the cases of norovirus was detected (p = 0.001). The IC kit provided high specificity (99.3 %) and sensitivity (100 %) for the detection of norovirus. Conclusions: This study will provide an integrated insight on the genotypic diversity and rapid identification method of norovirus in Bangladesh.